2012
DOI: 10.1063/1.4740053
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-monoenergetic protons accelerated by laser radiation pressure and shocks in thin gaseous targets

Abstract: Recent experiments and simulations have demonstrated effective CO 2 laser acceleration of quasimonoenergetic protons from thick gaseous hydrogen target (of thickness tens of laser wavelengths) via hole boring and shock accelerations. We present here an alternative novel acceleration scheme by combining laser radiation pressure acceleration with shock acceleration of protons in a thin gaseous target of thickness several laser wavelengths. The laser pushes the thin gaseous plasma forward while compressing it wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The scheme of laser RPA of quasi-monoenergetic protons has been actively studied in theory and simulations [11][12][13][14][15][16][17][18][19] and experiments. 20,21 In RPA, or equivalently "light sail," high intensity circularly polarized laser light with a high contrast ratio accelerates nearly the whole thin foil by the radiation pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The scheme of laser RPA of quasi-monoenergetic protons has been actively studied in theory and simulations [11][12][13][14][15][16][17][18][19] and experiments. 20,21 In RPA, or equivalently "light sail," high intensity circularly polarized laser light with a high contrast ratio accelerates nearly the whole thin foil by the radiation pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In order to acquire quasi-monoenergetic protons, the scheme of laser RPA has been actively studied in theory and simulations [18][19][20][21][22][23][24][25][26] and experiments. 27,28 In RPA, a high intensity circularly polarized laser beam irradiates an ultra-thin foil and accelerates nearly the whole foil by the radiation pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of laser acceleration of protons from a target foil, there are mainly two schemes being widely studied: target normal sheath acceleration [5][6][7][8][9][10][11][12][13][14] (TNSA) and radiation pressure acceleration (RPA). In particular, to acquire quasi-monoenergetic protons, the scheme of laser RPA has been actively studied in theory and simulations [15][16][17][18][19][20][21][22][23] and experiments [24][25][26]. In RPA in the light-sail region, a high intensity laser beam irradiates an overdense thin foil (or an overdense thin foil formed by laser radiation compression) and accelerates nearly the whole foil.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated, for example, that micrometer-sized nozzles and skimmers can be used to produce supersonic helium atom beams [36]. Previous numerical and experimental studies [23,37] showed that it is possible to produce high-energy quasi-monoenergetic proton beams from a gaseous hydrogen target accelerated by a CO 2 laser with a wavelength of 10 μm.…”
Section: Introductionmentioning
confidence: 99%